The Overview of Self-Efficacy Among Nursing Students - Retno Purwandari; Alfid Tri Afandi; Diyah Ayuningrum Amini; Anisah Ardiana; Dicky Endrian Kurniawan (Babali Nursing Research, 2023)
Self-efficacy in nursing students can affect the clinical and academic learning process. Self-efficacy is an assessment or belief that a person has about their ability to organize and carry out an action. This study aims to describe the self-efficacy of nursing students. The research design used was non-experimental with a descriptive approach. The population in this study were professional students of the Faculty of Nursing, the University of Jember, with a total sampling technique of 236 respondents. The results showed that the respondents' self-efficacy obtained the mean and standard deviation (60.75 ± 8.296). In the results of the self-efficacy indicator, the mean and min-max results for levels 23.96 and 9-32. The mean (18.79) and min-max (7-24) results are obtained on the strength indicator. The generalization indicator's mean (18.02) and min-max (10-24) results are obtained. The conclusion of this study shows that the value of student self-efficacy is still not optimal because students do not fully state that they often and very often have confidence in carrying out and completing the nursing professional education process. Students' self-efficacy needs to be improved by having good relationships with clinical and academic supervisors as role models, asking for verbal persuasion from those closest to them, and practicing activities independently to achieve a certain level of competence.